Role of Brain Structure in Predicting Adherence to a Physical Activity Regimen. Issue 1 (January 2018) - Gujral, Swathi; McAuley, Edward; Oberlin, Lauren E.; Kramer, Arthur F.; Erickson, Kirk I.
ABSTRACT: Objective: Physical activity (PA) is important for maintaining health throughout the lifespan. However, adherence to PA regimens is poor with approximately 50% of older adults terminating activity intervention programs within 6 months. In this study, we tested whether gray matter volume and white matter microstructural integrity before the initiation of a PA intervention predicts PA adherence. Methods: One hundred fifty-nine adults aged 60 to 80 years were randomly assigned to a moderate-intensity aerobic walking condition or a nonaerobic stretching and toning condition. Participants engaged in supervised exercise 3 times per week for 12 months. Data were collected for a period of 1 year. Voxel-based morphometry and tract-based spatial statistics protocols were used to process neuroimaging data, and ordinary least squares regression models with bootstrapping were used to analyze voxelwise neural predictors of PA adherence. Results: Greater volume in several regions predicted greater PA adherence, including prefrontal, motor, somatosensory, temporal, and parietal regions ( p < .01). We also found that higher fractional anisotropy in several white matter tracts predicted greater PA adherence ( p FDR-corrected < .05), including the superior longitudinal fasciculus, anterior thalamic radiation, forceps minor, and body of the corpus callosum. Conclusions: These findings provide preliminary support for macro- and microstructural neural predictors of PA adherence and may translate to other health behaviors and behavioral goal pursuit more broadly.